1324Clinical Registry for Acute Respiratory Infections in Children in Western Australia. (2nd September 2021) - Bhuiyan, Mejbah; Pavlos, Rebecca; O'Brien, Sharon; Borland, Meredith; Doyle, Sarah; Blyth, Christopher
Abstract: Background: Acute respiratory infections (ARIs) are the leading cause for emergency presentation and a major driver for antibiotic use in children. In 2020, we established an ARI clinical registry to: evaluate clinical care for ARI to inform clinical guidelines; and as a platform for clinical trials assessing antimicrobial interventions. Methods: Any child <16 years presenting to Perth Children's Hospital Emergency Department (ED) with cough, fever, sore throat and/or difficulty breathing was eligible for enrolment. Using an automated survey sent to parents' mobile phones, each enrolled child was followed weekly until 28 days or disease recovery (whichever occurred first). Data collected included clinical symptoms, antibiotic prescription, adherence, and duration to return to regular activity (recovery). Results: From Feb 2020-April 2021, 448 participants were enrolled (84% <5 years). Fever and cough were the most frequently reported symptoms. Of 448, 274 (61%) ARI cases completed all surveys until recovered. The median recovery length was 9 days (IQR:6-12). The recovery days were longer, although not statistically significant (p > 0.05), in: children who received antibiotics versus those who did not (9.5 days vs. 8); children <5 years versus those over (9 days vs. 7); and children with chronic illnesses versus those without (9 days vs. 8). Conclusions: Most children presenting to ED with ARI recover within 10 days. The length of recovery does not vary significantly by age, chronic illnesses, or antibiotic usage. Key messages: Registry data provides baseline data to inform clinical trials assessing the role and duration of antibiotics for ARI.